Ureteroscopy under General Anesthesia Versus Spinal Anesthesia: Stone Clearance and Morbidity - Aftab Ahmed Channa, Shumaila Ashfaq, Muhammad Zahid Ahmad, Muhammad Asif, Muhammad Waqar Shahid, Nauman Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare stone clearance by ureteroscopy carried out under General anesthesia versus Spinal anesthesia for the treatment of ureteric Stone. Place and duration: For two years from Feb 2019 to Feb 2022, in the Urology department of Islam Medical College Sialkot. Methods: Total 42 patients were selected for study. Males were 26, and Females were 16. Age ranges from 20 years to 56 years. All subjects endured ureteroscopic method for ureteric Stone with semi rigid ureteroscope 8/8.4 fr. The two groups of 21 patients equally were formed. Group A were given General Anesthesia and Group B receiving Spinal Anesthesia. The hospital stays, operative Time, clearance of stones, post-operative and intra operative complications were noted. Results: There were 21 patients in both groups, 16 (76.2%) men in group A (general anesthesia), and 18 (85.7%) men in group B (spinal anesthesia). There were 5 (23.8%) women in A group and 3 (14.3%) women in B group. The patients mean age was 34.1 and 37.2 years in groups A and B, correspondingly. The mean size of stone was 0.80 cm in A group and in group B, it was 1.21 cm (p = 0.001). The surgery duration in group A was 40.9 ± 1.30 mints and for group B; 31.4 ± 2.09 minutes (p = 0.031). The mean stay in hospital was 20.8 and 17.4 hours in groups A (range 8 to 48 hours) and B group (range 6 to 24 hours, p = 0.074), correspondingly (p = 0.073). The mean visual-analog pain score was 3.2 in group A and for group B, VAS was 1.7. Conclusion: In this series, ureteroscopy under spinal anesthesia shortened the duration of surgery and hospital stay and did not carry the risk of additional serious complications.